The Temporal Metaphors of Shakespeare’s Sonnets: A Cognitive Perspective - Mufeed Al-Abdullah (Progress in Language, Literature and Education Research Vol. 9, 2024)
The article studies the conceptual metaphors of time in the sonnets of Shakespeare in light of the Conceptual Metaphor Theory (CMT) of Lakoff and Johnson [1] presented in their book, Metaphors We Live By, and Kovecses’ [2] informative views in his book, Metaphor: A Practical Introduction. The sonnets of Shakespeare also reflect some of St. Augustine’s views on the passage of time, which divide time into the three components of past, present, and future. Indeed, the subject of time is a pervasive theme in the sonnets of Shakespeare. The extracted metaphors selected from a variety of sonnets that tackle the theme of time will be divided into three sub-categories: structural, ontological, and orientational. Using the cognitive approach to understand the abstract concept of time in terms of a variety of concrete concepts with an experiential dimension allows the reader to perceive this concept from different perspectives. Under ontological metaphors, the study addresses metaphors in the forms of personification, metonymy, and synecdoche. The study endeavors to show that the cluster of source domains Shakespeare provides in the metaphors map an association of multidimensional possibilities that improve our understanding of time. Also, this consortium of possibilities points to the creativity and wide scope of Shakespeare’s vision. The study hopes to add another vantage point from which to view Shakespeare’s presentation of time in light of modern progress in the studies of conceptual metaphors and cognitive poetics. Shakespeare’s creativity expands the human consciousness of time and initiates more perspectives from which to evaluate the human experience with that concept. These perspectives are based on the human experience of nature, society, and culture.